Design and simulation of a smart master switch system based on multi-input XOR logic gate - Jimmy Nabende Wanzala; Michael Robson Atim (Discover Electronics)
Abstract Mechanical switches have been the conventional way of controlling electrical energy in different electrical systems such as: lighting systems, socket systems, and circuit breakers, especially in domestic, hospital, and industrial applications. Mechanical switches often require physical access to control different electrical devices that are connected to the power sources. The work presented in this paper aimed at designing and simulating a multi-input based Exclusive-Or master switch system that remotely controls the lighting and socket systems using the wireless switching mechanisms of Global System for Mobile communication and Bluetooth. The system therefore limits physical interaction that require use of the single pole double throw and keypad mechanical switches that are however included to act as fall-back mechanism in control of electrical devices. Within the recommended electrical safety measures, the design can be streamlined and integrated to remotely control lighting systems and sockets alongside the conventional mechanical switches in the consumer control unit.